2018
DOI: 10.1001/jamaneurol.2018.2017
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effects on the Neurologic Pain Signature

Abstract: for the Placebo Imaging Consortium IMPORTANCE Placebo effects reduce pain and contribute to clinical analgesia, but after decades of research, it remains unclear whether placebo treatments mainly affect nociceptive processes or other processes associated with pain evaluation.OBJECTIVE We conducted a systematic, participant-level meta-analysis to test the effect of placebo treatments on pain-associated functional neuroimaging responses in the neurologic pain signature (NPS), a multivariate brain pattern trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 84 publications
8
95
0
Order By: Relevance
“…1D). Thus, placebo successfully decreased subjective pain intensity with an effect size similar to previous placebo analgesia neuroimaging studies (Zunhammer et al, 2018).…”
Section: Expectations In Medication Effectiveness and Individual Painsupporting
confidence: 79%
See 1 more Smart Citation
“…1D). Thus, placebo successfully decreased subjective pain intensity with an effect size similar to previous placebo analgesia neuroimaging studies (Zunhammer et al, 2018).…”
Section: Expectations In Medication Effectiveness and Individual Painsupporting
confidence: 79%
“…This is in line with findings from Petrovic and colleagues (2002) who demonstrated similar engagement of rACC and brainstem in both placebo and opioid analgesia. Increased activation of brainstem, thalamus, striatal regions, dorsal and rostral ACC, and the insula (IC 22) might thus reflect placebo-induced, opioidergic activation related to the top-down modulation of pain (Baumgärtner et al, 2006;Eippert et al, 2009;Zunhammer et al, 2018). Most importantly, we found these connectivity changes during resting-state, in absence of actual pain anticipation or perception.…”
Section: Discussionmentioning
confidence: 62%
“…Evidence also strongly suggests that placebo treatments are unlikely to directly modulate bottom-up sensory signals, but rather are influencing high level top-down processes 121. Therefore, predictive coding/bayesian brain contends that in acute pain, placebos can influence pain perception through the induction of top-down expectations of pain, transiently biasing the bayesian computation toward this prediction.…”
Section: Evidence For Theories Of Placebo Effectsmentioning
confidence: 99%
“…Both explicit suggestions and placebo responses are due to top-down mechanisms (Zunhammer et al, 2018 ), but it has been shown that, in correspondence of similar subjective response to expectation-induced placebo, highs and lows exhibit opposite patterns of activity and functional connectivity (Huber et al, 2013 ). In fact, the former exhibit reduced functional connectivity between the right dorsolateral prefrontal cortex (rDLPC) and the anterior midcingulate/medial prefrontal cortex, the left inferior frontal gyrus and the right cerebellum.…”
Section: Hypnotizability and Expectation Of Pain Reliefmentioning
confidence: 99%